Pengaruh Pengetahuan dan Brand Image Bank Syariah terhadap Minat Menabung Santri Pondok Pesantren di Kabupaten Bangka - Fazaria Fazaria; Hendra Cipta; Mahfudz Reza Fahlevi (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
Knowledge of sharia banks andbrand image has an important role for the survival of an Islamic bank. Islamic banking is a service industry that carries out its business activities based on Islamic principles. The majority of Indonesians, including Muslim entrepreneurs, to students like the santri choose Islamic banks to conduct transactions based on an understanding of Islamic banking and brand image. This makes the students interested in saving in Islamic banks. However, based on previous knowledge and researchbrand image have influence but not significant. This study aims to review and analyze the effect of knowledge andbrand image sharia banks on the interest of Islamic boarding school students in saving in Bangka Regency. The research used is quantitative research with techniquessimple random sampling, while for data measurement usingscale likert. Data collection techniques used are questionnaires and documentation. Data analysis techniques using descriptive statistics and inferential statistics (validity test, reliability test, classical assumption test, multiple linear regression test and hypothesis testing). The results of this study indicate that the knowledge variable influences the intention to save Islamic boarding school students in Bangka Regency, with a value of tcount(5,128) > ttable(1.652142), with a significance level of 0.000 <0.05. Variablebrand image effect on the intention to save Islamic boarding school students in Bangka regency, with a value of tcount(6,319) > ttable(1.652142), with a significance level of 0.000 <0.05. Variable knowledge andbrand image simultaneously influencing the intention to save Islamic boarding school students in Bangka Regency, with a value of Fcount(86,236) > Ftable(3,04).